Home page for accesible maths 6 Chapter 6 contents

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

6.17 Solution

On integrating, we have

ex2y=xex2dxe^{x^{2}}y=\int xe^{x^{2}}\,dx

which equals 12ex2+c\frac{1}{2}e^{x^{2}}+c. Dividing both sides by ex2e^{x^{2}}, we obtain solutions y=12+ce-x2y={\frac{1}{2}+ce^{-x^{2}}} where cc is an arbitrary constant.

Let’s verify that this gives a solution of the equation: we have dydx=-2cxe-x2,\frac{dy}{dx}={-2cxe^{-x^{2}},} so

dydx+2xy=-2cxe-x2+x+2xce-x2=x\frac{dy}{dx}+2xy={-2cxe^{-x^{2}}+x+2xce^{-x^{2}}=x}

as required.